LECTURER'S PERCEPTION OF STUDENT'S ABILITY PANDANARAN UNIVERSITY IN ONLINE LEARNING - Adji Seputra; Dheasey Amboningtyas (Jurnal Ekonomi, 2022)
This type of research is a survey research using three data collection techniques are questionnaires, documentation, and interviews. The variables studied were the Lecturer’s Perception of Creative Thinking Ability X1; Lecturer’s Perception of Logical Thinking Ability (X2); and Student Ability in Virtual Class and WhatsApp Group Online Learning (Y). The results showed that (1) Lecturer’s Perception of Creative Thinking Ability (X1) had a significant effect on Ability in Online Learning Virtual Class and WhatsApp Group with the Standardized Coefficients value of 0.958 or 95.8%. This means that the Lecturer’s Perception of Creative Thinking Ability 95.8% influences Ability in Virtual Class and WhatsApp Group Online Learning; (2) Lecturer’s Perception of Logical Thinking Ability (X2) has a significant effect on Ability in Online Learning Virtual Class and WhatsApp Group with the Standardized Coefficients value of 0.045 or 4.5%. This shows that Logical Thinking Ability (X2) influences Ability in Virtual Class and WhatsApp Group Online Learning.